Implementing Problem-Based Learning to Improve Understanding of QS. Al Maun and Social Awareness - Riza Arfani; Ulul Albab (Research Journal on Teacher Professional Development, 2026)
This study aims to analyze the improvement of learning outcomes in Islamic Religious Education and Character Education (PAI and BP), specifically the material of QS. Al Maun and "Living Spaciously by Sharing," through the application of the Problem Based Learning (PBL) model. This study uses a Classroom Action Research (CAR) approach with the Kemmis and McTaggart spiral model consisting of planning, implementation, observation, and reflection stages in each action cycle. The study was conducted in three cycles with elementary school students as subjects. The results showed that the application of the Problem Based Learning model succeeded in improving student learning outcomes significantly. Before the action was carried out, the average student score only reached 68.4 with a learning completion of 43.4%. After the implementation of PBL in Cycle I, the average score increased to 76.8 with a completion of 65.2%. In Cycle II, the average score increased again to 83.7 with a completion of 82.6%, and reached optimal results in Cycle III with an average score of 89.5 and a learning completion of 95.6%. In addition to improving cognitive aspects, this study also demonstrated positive changes in students' social activities and attitudes. Students became more active in discussions, expressed their opinions confidently, were able to work collaboratively in groups, and developed a stronger sense of responsibility throughout the learning process. The use of contextual problems, interactive media, and role-sharing within groups were proven to improve students' learning motivation and communication skills. Furthermore, students demonstrated increased empathy, social awareness, and a spirit of sharing, in line with the values ​​contained in QS. Al-Ma'un. Thus, the Problem-Based Learning model is effective in improving learning outcomes while optimally shaping students' social character. The contribution of this study is to provide an innovative learning model based on Problem-Based Learning that is effective in improving learning outcomes, collaborative skills, and developing students' social character in Islamic Religious Education (PAI) and Islamic Religious Education (BP) in elementary schools. Keywords: problem-based learning, QS. Al-Ma'un, social awareness